Synthesis of Multi-Walled Carbon Nanotubes Modified Rutile (TiO2/MWCNTs) Composite for Photocatalytic Degradation of Textile Wastewater - Adewoye, Tunmise Latifat; Issa, Omowumi Mardiyah; Mohammed, Ishaq Alhassan; Mustapha, Sherif Ishola; Eletta, Omodele Abiodun Abosede; Aderibigbe, Fatai Alade; Abdulkareem, Saka Ambali (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Photocatalysis has emerged as a sustainable and efficient approach for the treatment of industrial wastewater, offering the potential to degrade persistent organic pollutants under light irradiation. This study explores the enhanced photocatalytic degradation of textile wastewater using a TiO2-based nanocomposite photocatalyst. The composite was synthesized by modifying rutile TiO2, derived from natural rutile ore, with multi-walled carbon nanotubes (MWCNTs) through a hydrothermal process. The microstructure, morphology, chemical composition, surface area, and phase structure of rutile-TiO2, MWCNTs, and the TiO2/MWCNTs nanocomposite were characterized using different characterization techniques including high-resolution transmission electron microscopy (HRTEM), high-resolution scanning electron microscopy (HRSEM), UV-Vis spectroscopy, Brunauer-Emmett-Teller (BET) surface area analysis, and X-ray diffraction (XRD). Photocatalytic activity was evaluated by measuring the degradation of organic pollutants, with chemical oxygen demand (COD) and phenol concentration as indicators, under both artificial and natural sunlight irradiations. The results revealed that the incorporation of MWCNTs significantly enhanced the photocatalytic performance of rutile TiO2. Under visible light, phenol removal efficiencies were 59% and 42% for the TiO2/MWCNTs nanocomposite and rutile-TiO2, respectively, while under sunlight, the removal rates increased to 73% and 56%. Similarly, COD reduction was 55% for TiO2/MWCNTs compared to 35% for rutile-TiO2 under visible light, and 73% versus 56% under sunlight. These findings demonstrate that MWCNT modification improves the photoactivity of rutile-TiO2, offering a cost-effective and sustainable approach to wastewater treatment using photocatalysts derived from natural ore. This study presents a viable alternative for synthesizing TiO2-based materials for environmental remediation.